2018
DOI: 10.1139/cjfas-2017-0293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a single genomic region associated with seasonal river return timing in adult Scottish Atlantic salmon (Salmo salar), using a genome-wide association study

Abstract: Examination of the genetic basis of the timing of the return migration of Atlantic salmon (Salmo salar) to fresh water from the sea, a trait of economic and conservation interest, was carried out using a genome-wide association study. We examined genotype data of 52 731 single nucleotide polymorphic (SNP) markers from 73 early and 49 late running two-sea-winter salmon from five rivers in eastern Scotland. A single region of the Atlantic salmon chromosome Ssa09 was identified, containing nine SNP markers signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 66 publications
(23 reference statements)
6
35
0
Order By: Relevance
“…Likewise, during their return migration, Atlantic salmon may be non-randomly distributed in relation to their life history, genotype, and population of origin (Svenning et al 2019). For example, relatively early run timing is linked to both later maturation (Jonsson and Jonsson 2011) and six6*L (Cauwelier et al 2018, Pritchard et al 2018), a pattern that concordantly holds in our dataset (Supp. Table 11).…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, during their return migration, Atlantic salmon may be non-randomly distributed in relation to their life history, genotype, and population of origin (Svenning et al 2019). For example, relatively early run timing is linked to both later maturation (Jonsson and Jonsson 2011) and six6*L (Cauwelier et al 2018, Pritchard et al 2018), a pattern that concordantly holds in our dataset (Supp. Table 11).…”
Section: Discussionsupporting
confidence: 82%
“…() also found a small but significant effect of genotype at this locus on length of returning adults. Recently, Cauwelier, Gilbey, Sampayo, Stradmeyer, and Middlemas () found that the locus was associated with intrapopulation variation in run timing of Atlantic salmon in Scotland. Further, Bourret, Dionne, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of salmonids have found genome-wide differences between populations and ecological morphs. Significant genetic differences were found between migratory and non-migratory Rainbow trout (Hale et al 2013), the lake, river and stream ecotypes of sockeye salmon (Larson et al 2017) and ecologically different subpopulations of salmon (Vincent et al 2013;Cauwelier et al 2017). Sympatric ecotypes are found in several salmonid species, e.g.…”
Section: Genome-wide Separation Of Sympatric Morphsmentioning
confidence: 99%